2020
DOI: 10.3389/fmats.2020.590661
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Design of High-Strength Concrete Mix Proportion for Crack Resistance Using Artificial Neural Networks and Genetic Algorithm

Abstract: The fact that high-strength concrete is easily to crack has a significant negative impact on its durability and strength. This paper gives an optimum design method of high-strength concrete for improving crack resistance based on orthogonal test artificial neural networks (ANN) and genetic algorithm. First, orthogonal test is operated to determine the influence of the concrete mix proportion to the slump, compressive strength, tensile strength, and elastic modulus, followed by calculating and predicting the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In comparison to other studies, Yue et al [97] developed an ANN model to predict fc, ft, elastic modulus, and concrete slump. The resulting R 2 values obtained for these properties were above 0.94.…”
Section: Results and Discussion Of The Ann Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other studies, Yue et al [97] developed an ANN model to predict fc, ft, elastic modulus, and concrete slump. The resulting R 2 values obtained for these properties were above 0.94.…”
Section: Results and Discussion Of The Ann Modelsmentioning
confidence: 99%
“…Table7shows the results of the combined ANN model for predicting the properties of concrete. The R 2 values of fc, ft, and PV obtained through this model are above 0.9, reflecting higher prediction accuracy.In comparison to other studies, Yue et al[97] developed an ANN model to predict fc, ft, elastic modulus, and concrete slump. The resulting R 2 values obtained for these properties were above 0.94.…”
mentioning
confidence: 99%
“…where σ t (t) is the deformation tensile stress (cracking driving force) of concrete at the early age t, MPa; f t (t) is the tensile strength of concrete at the early age t, MPa; E (t) is the elastic modulus of the concrete at the early age t, MPa; ε sh−e (t) is the effective shrinkage strain of the concrete at the early age t. Among them, when η < 0.7, the concrete does not crack; when 0.7 ≤ η ≤ 1.0, the concrete may crack; when η > 1.0, the concrete cracks. Gao et al's [22,23] research showed that the effective shrinkage strain ε sh−e (t) was the result of the interaction of the shrinkage strain and the creep strain (strain of concrete due to creep) of the concrete, as shown in…”
Section: E Establishment Of Early Cracking Risk Prediction Model Of Concretementioning
confidence: 99%
“…where t and t 0 are the age of concrete and the age of concrete under loading, respectively, d; ε sh (t) is the shrinkage strain of the concrete at the age t; ε creep (t, t 0 ) is the shrinkage strain of the concrete due to creep in the early age (t, t 0 ). Bentz et al's [9,23] study showed that the relationship between creep strain and effective shrinkage strain can be expressed by creep coefficient φ, as shown in…”
Section: E Establishment Of Early Cracking Risk Prediction Model Of Concretementioning
confidence: 99%
“…Analytical methods help obtain the optimal concrete mixes based on in-depth and extensive experimental knowledge of certain heavy components and the fundamental formulae obtained from past experiments [30][31][32][33]. For example, artificial neural networks, genetic algorithms, and mathematical programming are tools for evaluating semi-experimental (analytic) methods based on a combination of experimental databases or predictive models developed for trial [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%